Apoplastic class III peroxidases PRX62 and PRX69 regulate ROS-homeostasis and cell wall associated extensins linked to root hair growth at low-temperature in Arabidopsis thaliana - Martinez Pacheco, Javier (2021)
Root hairs (RH) growth is highly influenced by endogenous as well as by external environmental signals that coordinately regulate its final cell size. RHs actively expand the root surface responsible for nutrient uptake and water absorption. We have recently determined that RH growth was unexpectedly boosted when Arabidopsis thaliana seedlings are cultivated at low temperatures. It was proposed that RH growth plasticity in response to cold was linked to a reduced nutrient availability in the media. Here, we explored the molecular basis of this strong RH growth response by using the Genome Wide Association Studies (GWAS) approach on Arabidopsis thaliana natural accessions. We identified the poorly characterized PEROXIDASE 62 (PRX62) as a key protein triggering this conditional growth under a moderate low-temperature stress. In addition, we identified the related protein PRX69 as an important factor in this developmental process. The prx62 prx69 double mutant and the PRX62 and PRX69 over-expressing lines showed contrasting RH phenotypes, peroxidase activities and cyt/apoReactive Oxygen Species (ROS) levels. Strikingly, a cell wall protein extensin (EXT) reporter revealed the effect of peroxidase activity on the EXT cell wall association at 10C in the RH apical zone. EXT cell wall insolubilization was enhanced at 10C, which was completely abolished under the PRX inhibitor salicylhydroxamic acid (SHAM) treatment. Finally, we demonstrated that the Root Hair defective 6 like 4 (RSL4) transcription factor directly controls the expression of PRX69 under low-temperature. Collectively, our results indicate that both PRX62 and PRX69 are key apoplastic PRXs that modulate ROS-homeostasis and cell wall EXT-insolubilization linked to RH elongation at low-temperature.